Ministry Of Finance Decree No. 160 of the Year 2020 Amending Certain Provisions of the Executive Regulations of the Value-Added Tax Law Promulgated by Decree No. 66 of the Year 2017 = وزارة المالية قرار رقم 160 لسنة 2020 بتعديل بعض أحكام اللائحة التنفيذية لقانون الضريبة على القيمة المضافة الصادرة بقرار وزير المالية رقم 66 لسنة 2017 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic